O uso de sequências didáticas investigativas como proposta para o estudo do conceito de velocidade em uma escola pública de Manaus - Souza, Everson Apolinário de (2018)
The development of alternative conceptions in the sense of scientific knowledge is a gradual and extensive evolution. The reason for this is that such ideas are harmonious, global, stubborn, and solid (PINTÓ, et al., 1996). Several researchers have emphasized the collaborations of the use of these activities for the conceptual development (AZEVEDO, 2006; CARVALHO, 2013; BORGES, 2002). A study was carried out on the collaborations of these activities for the development of the concept of speed. This study was carried out in the first semester of 2018 with students of the first year of High School who had already studied the content of kinematics. Most of them showed alternative conception, which proves that this way of knowing can occur even after formal education. Three activities were carried out that put the students in front of several events in order to generate cognitive conflict (CARVALHO, 1992). The students' written products were collected and analyzed using the content analysis as a guide (BARDIN, 1977). It was demonstrated that the investigative activities performed are an excellent option to the classic laboratory classes and presented potential in the promotion of the development of the alternative conceptions.